1988
DOI: 10.3354/meps048081
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of marine meiofauna. Areview and conceptual model explaining passive transport and active emergence with implications for recruitment

Abstract: A number of recent studies have shown that water-column processes exert an important influence on meiofaunal recruitment and colonization of new areas. T h~s paper reviews those studies which have investigated the water-column occurrence of meiofauna and the subsequent settlement process. Two distinct patterns exist for recruitment via water-column pathways: active entry of meiofauna into the water and passive erosion of meiofauna from the sediments. A conceptual model is proposed in which 4 factors interact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
184
1
4

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(193 citation statements)
references
References 42 publications
(71 reference statements)
4
184
1
4
Order By: Relevance
“…Colonisation by invertebrates is rapid, however, it is limited in its extent and magnitude (Norkko and Bonsdorff, 1996;Palmer, 1988). For that reason active migration or passive dispersion towards macrophytodetritus accumulations was not sufficient to explain comparable quantities and diversities.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…Colonisation by invertebrates is rapid, however, it is limited in its extent and magnitude (Norkko and Bonsdorff, 1996;Palmer, 1988). For that reason active migration or passive dispersion towards macrophytodetritus accumulations was not sufficient to explain comparable quantities and diversities.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…However, recent investigations revealed that at least some meiofaunal taxa may actively leave the sediment and swim in the water column (Alldredge & King, 1977;Hobson & Chess, 1979;Hammer, 1981;Sibert, 1981;Ohlhorst, 1982;Hicks, 1986;Walters & Bell, 1986; recently reviewed by Palmer, 1988). Most of these studies deal with tropical to warm temperate subtidal habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Butman et al 1988, Snelgrove et al 1993 suggest that in weak flows, small fauna can easily move locally, e.g. on the cm scale, as well as distantly (Palmer 1988, Stocks 2002. Thus, avoidance of disturbed areas by new recruits, and local movement to a more favorable area (Snelgrove et al 2001a), may enhance survival in a habitat where adult conspecifics thrive.…”
Section: Disturbance Habitat Selection and Community Structurementioning
confidence: 99%